Evaluation of strawberry (Fragaria L.) genetic resources for resistance to Botrytis cinerea. (12th August 2014) - Bestfleisch, M.; Luderer‐Pflimpfl, M.; Höfer, M.; Schulte, E.; Wünsche, J. N.; Hanke, M.‐V.; Flachowsky, H.
<x xml:space="preserve">Abstract</x> The grey mould disease caused by Botrytis cinerea leads to substantial economic losses in strawberry production all over the world. Control of the disease requires an extensive amount of fungicide that is applied in varying complexes because the pathogen easily develops resistance against the active compounds. Planting of resistant cultivars seems to be a promising alternative for fruit growers, but there are currently no cultivars available combining resistance to B. cinerea with attractive horticultural traits. Breeding of new cultivars requires the effective identification of resistant strawberry genotypes; therefore the current study was aimed at the evaluation of strawberry genetic resources under controlled conditions by establishing an artificial inoculation assay. The method presented in this study is an artificial inoculation of ripe fruits with a defined spore suspension under laboratory conditions. The results show that this assay is fast and simple and leads to reproducible results that correlate with field observations. Over 3 years a total of 107 strawberry genotypes of the German National Fruit Genebank at the JKI in Dresden‐Pillnitz were evaluated. Five partly resistant genotypes, cultivars Diana, Joerica and Kimberly, and Fragaria virginiana 'Wildmare Creek' and F. vesca subsp. bracteata, were identified with mean disease levels of <20% at 6 days post‐inoculation. The obtained results are discussed with regard to future breeding activities.